2017
DOI: 10.1002/lio2.88
|View full text |Cite
|
Sign up to set email alerts
|

Progressive resistance training in head and neck cancer patients undergoing concomitant chemoradiotherapy

Abstract: ObjectivesPatients with head and neck squamous cell carcinoma undergoing concomitant chemoradiotherapy (CCRT) frequently experience weight loss, especially loss of lean body mass (LBM), and reduced functional performance. This study investigated whether a 12‐week hospital‐based progressive resistance training (PRT) program during CCRT is feasible in the clinical setting before planning initiation of a larger randomized study which is the long‐term goal.Study designProspective pilot study.MethodsTwelve patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
(91 reference statements)
1
16
0
Order By: Relevance
“…A total of 41 studies were included in this review, with different methodologies: one systematic review (16), one consensus paper (17), one data descriptor (18), nine randomized trials (6, 11, 1925), 12 cohort studies (3, 79, 15, 2632), three randomized controlled trials (4, 5, 33), three cross-sectional studies (3436), two prospective non-randomized trials (37, 38), eight retrospective studies (10, 1214, 3942), and one case-control study (43).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 41 studies were included in this review, with different methodologies: one systematic review (16), one consensus paper (17), one data descriptor (18), nine randomized trials (6, 11, 1925), 12 cohort studies (3, 79, 15, 2632), three randomized controlled trials (4, 5, 33), three cross-sectional studies (3436), two prospective non-randomized trials (37, 38), eight retrospective studies (10, 1214, 3942), and one case-control study (43).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors suggest that ~70% of the weight loss identified in HNC patients corresponds to lean body mass (LBM) (46). Loss of LBM has been presented as an important prognostic factor (4, 7) with influence in treatment toxicities (8), risk of recurrence and mortality (9), impaired muscle strength, a decline in physical activity and functional performance (6). It seems that, in HNC patients, LBM depletion may provide additional and relevant information as an outcome predictor beside weight loss alone and furthermore, high BMI, and low LBM may associate with each other (10).…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck tumor demonstrate a high prevalence when related to severe and not severe WL, with a discrepancy of 37 and 15 individual. Patients with head and neck cancer often present WL, especially the loss of lean mass and functional performance (Lonkvist et al, 2017). In Webster et al (2018), study, with a population composed of 666 patients diagnosed with oropharyngeal cancer during the years 2004 to 2017, the patients presented 30,3% WL during oncological treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in skeletal muscle and lean body mass [41][42][43][44] Improvement in fatigue and acute QoL symptom management.…”
Section: Reduced Exercise Resistance Trainingmentioning
confidence: 99%